Strategy at Scandinavian architectural firm - LAPTHANANCHAIWONG, THONGCHAI (My University, 2017)
This research focuses on strategy that a Swedish architectural firm performs in order for internationalizing into Scandinavian market. The Scandinavian market is comprised of three countries which are Sweden, Denmark and Norway. These countries have both similarity and difference which provide opportunity for business and industry to have expansion and growth. The research is framed by based on three areas of literature which are business of architectural firm, internationalization and strategy. The literature in business of architectural firm is described as fundamental ground. The internationalization is as a key to the study. Both are seen and elaborated through a lens which provides strategic perspective for the analysis and finding. The empirical materials have been derived from a small-sized Swedish architectural firm. It is mainly carried out through semi-structure interview with additional desktop research. The finding indicates that, when a Swedish architectural firm internationalizes into Scandinavian market, the firm has to strategize for three key factors according to three dimensions of strategy. The first is in terms of business. The firm need to have product or service that is needed by cross-border clients. Secondly, it is opportunity as process. The firm has to seize the opportunity to access to crossborder market. In this aspect, flexibility and adaptation is needed. Thirdly, the firm has to execute international project as for creating of synergy and customizing the service to cross-border client. Those factors need to be strategized. In addition, the strategizing has to be specific, fit, flexible and harmonize with holistic situation.
Keywords: Samhällsbyggnadsteknik; Civil Engineering